(untitled) (UKLO Proceedings, 2026)
Introduction: In today’s world, increasingly afflicted by inequality, climate change, and governance problems, the United Nations Sustainable Development Goals (UN SDGs) underscore the necessity of fostering inclusive and sustainable societies. Digital technologies provide a critical avenue for realizing these objectives and Estonia, a small Baltic nation, stands as an exemplary global example of this potential. Methods: This qualitative case study uses a narrative approach to explore how the Estonian national government utilized digital technology to digitize public administration, including in the domains of education, taxation, and justice, with the aim of fostering inclusive and sustainable societies, drawing on peer-reviewed studies, government records, and industry reports. The study also underscores the nation’s steadfast commitment to safeguarding privacy and cybersecurity, while also highlighting, scaling and sustainability challenges currently experienced by the nation. Results and Discussion: The findings of the study indicate that Estonia’s e-governance, facilitated by digital technologies and characterized by features such as e-voting, e-education, e-health, e-ID, e-residency, e-business tools, e-justice, and data embassy has enhanced public engagement, decreased operational expenses, and mitigated environmental effects. These results highlight how a government driven by digital technology is guiding the nation towards greater inclusivity and sustainability. Additionally, it emphasizes that inter-sectoral collaboration and strategic approaches to improve cyber resilience is crucial to the success of e-governance and ultimately to the establishment of inclusive and sustainable societies. The study concludes that Estonia’s e-governance has helped establish inclusive and sustainable societies and furthered equitable and sustainable development in accordance with the United Nations Sustainable Development Goals, including SDG 9 (Industry, Innovation and Infrastructure), SDG 10 (Reduced Inequalities), and SDG 16 (Peace, Justice and Strong Institutions). It underscores equitable practices, strong inter-sectoral collaboration and strategic and proactive governance are crucial for enabling technology-driven public administration. Originality and Value: Building inclusive and sustainable societies is increasingly significant, in today’s world where governments are seeking governance frameworks that are transparent, effective, and people-oriented. This study offers policy makers and strategists of other nations much-needed guidance on how digital technologies can be leveraged to improve public administration for building inclusive and sustainable societies.